Synthesis Candidates Herbicide Through Optimization Quinclorac Containing 3-Methyl-1H-pyrazol-5-yl - Luo, Dingfeng; Bai, Haodong; Zhou, Xiaomao; Wu, Lamei; Zhang, Chengjia; Wu, Zhongchi; Li, Zuren; Bai, Lianyang (Frontiers in Chemistry, 2021)
To enhance quinclorac potency, twenty-five derivatives were synthesized containing 3-methyl-1H-pyrazol-5-yl by intermediate derivatization methods (IDMs). These compounds were confirmed by melting point (mp), 1HNMR, 13CNMR, HRMS. The compound 1,3-dimethyl-1H-pyrazol-5-yl 3,7-dichloroquinoline-8-carboxylate (10a) was determined by X-ray diffraction. The herbicidal activity of these compounds substituent on the phenyl was: electron-drawing group > neutral group > donor-drawing group, the results was like that of substituted benzyl group on pyrazole. The herbicidal activity assays shown that compound 1-(2-fluorophenyl)-3-methyl-1H-pyrazol-5-yl 3,7-dichloroquinoline-8-carboxylate (8l, EC50 =10.53 g / ha) and 10a (EC50 =10.37 g / ha) had excellent inhibition effect on barnyard grass in green house experiment. Rice safety tests exhibited almost no difference in plant height and fresh weight treated 10a at stage 1~2-leaf of rice after 14 days but 8l had a detrimental effect. Two seasons field assays shown 10a herbicidal activity on barnyard grass at 150 g / ha as equal as 300 g / ha quinclorac in fields in 2019 and 2020. The study demonstrated that 10a could be further researched as potential herbicide to control barnyard grass in fields.